Efficacy of a guided internet-based intervention (iSOMA) for somatic symptoms and related distress in university students: study protocol of a randomised controlled trial. Issue 12 (31st December 2018) - Hennemann, Severin; Böhme, Katja; Baumeister, Harald; Bendig, Eileen; Kleinstäuber, Maria; Ebert, David Daniel; Witthöft, Michael
Abstract : Introduction: Persistent and distressing somatic symptoms are common in younger age cohorts such as university students. However, the majority does not receive adequate psychosocial care. Internet-based and mobile-based interventions may represent low threshold and effective extensions to reduce somatic and associated mental symptom severity. The planned study aims to investigate the feasibility and efficacy of an internet-based intervention in reducing somatic and psychological symptoms in an international population of university students with somatic symptom burden. Methods and analysis: This parallel two-armed randomised controlled trial evaluates an 8-week guided intervention, including web-based consecutive modules based on cognitive behavioural therapy (CBT) principles against a waitlist control group. Guidance will be provided by trained psychologists with weekly written supportive feedback. As part of the 'Studicare' project, the present study aims to recruit n=154 university students indicating somatic symptom burden at baseline in German-speaking universities. Self-report assessments will take place at baseline and after intervention completion (8, 16 weeks after randomisation). The primary outcome will be the severity of somatic symptoms and associated mental distress. Secondary outcomes include depression, (health) anxiety, disability, intervention satisfaction and adherence. Ethics and dissemination: Ethics approval has been granted. Results from this study will be published in peer-reviewed journals and presented at international conferences. Trial registration number: DRKS00014375; Pre-results.